A benzimidazolyl‐substituted cyclotriphosphazene and its application in benzoxazine: Curing behaviors, thermal properties, and fire safety. Issue 5 (20th November 2022) - Wu, Feifan; Wang, Jun; Wang, Jingsheng; Chen, Kaiwen; Yang, Shuang; Huo, Siqi; Wang, Hao
Abstract: In this study, a well‐designed benzimidazolyl‐substituted cyclotriphosphazene (BICP) was used as a versatile additive to enhance the integrated performances of bisphenol A‐aniline based benzoxazine (BA‐a). Our results showed that the BA‐a/BICP systems possessed lower curing temperature than virgin BA‐a due to the catalytic action of tertiary amines in BICP. Moreover, the thermal resistance of BA‐a/BICP thermosets was better than that of BA‐a thermoset because of the rigid structure and high thermal stability of BICP. The introduction of BICP significantly enhanced the fire safety of BA‐a. For instance, the limiting oxygen index and UL‐94 rating of BA‐a/BICP‐11 sample with 11 wt% of BICP were up to 35.2% and V‐0. Compared with BA‐a, the total smoke production and peak smoke production rate of BA‐a/BICP‐17 sample with 17 wt% of BICP were reduced by 36.5% and 39.3%, respectively. The improved fire safety of BA‐a/BICP sample was mainly due to the condensed‐phase effect of BICP. This work provides a simple strategy for the development of advanced benzoxazine resins with low curing temperature, great thermal properties, and superior fire safety. Abstract :